The rates of quinolone, trimethoprim/sulfamethoxazole and aminoglycoside resistance among Enterobacteriaceae isolated from urinary tract infections in Azerbaijan, Iran - Yekani, Mina; Baghi, Hossein Bannazadeh; Sefidan, Fatemeh Yeganeh; Azargun, Robab; Memar, Mohammad Yousef; Ghotaslou, Reza (German Medical Science GMS Publishing House, 2018)
Aim: Antibiotic susceptibility patterns help to select appropriate empirical treatments of urinary tract infections (UTIs). This study aimed to investigate antibiotic resistance among Enterobacteriaceae isolated from UTIs in Azerbaijan, Iran.Methods: This study was carried out during 2016 in hospitals located in Tabriz, Urmia, and Khoy. Midstream urine specimens were cultured and identified by the standard methods. Susceptibility testing was carried out using the disk diffusion agar method for cefotaxime, ceftazidime, ceftriaxone, cefoxitin, imipenem, meropenem, ertapenem, cefepime, ampicillin, cefazolin, cefuroxime, aztreonam, nitrofurantoin, and fosfomycin and the agar dilution method for MIC determination of aminoglycosides, quinolones, sulfamethoxazole, and trimethoprim. Results: A total of 219 non-duplicated Enterobacteriaceae were isolated from UTIs. According to the agar dilution assay, the following resistance rates were determined: trimethoprim/sulfamethoxazole (co-trimoxazole) 69.8%, nalidixic acid 68.9%, ciprofloxacin 66.2%, levofloxacin 58.5%, tobramycin 47.9%, kanamycin 39.3%, gentamicin 27.8%, and amikacin 5.5%. High levels of resistance were observed to trimethoprim (78.5%), sulfamethoxazole (88.1%), ampicillin (86.3%), and cephazoline (79.4%). Conclusion: The most effective agents against Enterobacteriaceae were fosfomycin, carbapenems, and amikacin. Quinolones, trimethoprim and sulfamethoxazole are not appropriate for empirical therapy due to high levels of resistance. Amikacin is more effective among aminoglycosides and may be more effective, in complicated cases, when used in combination with fosfomycin and carbapenems.